Characterization of muscle activation intensity during barefoot running in non-adapted subjects - Azevedo, A. P.; Valvassori, R.; Mezêncio, B.; Claudino, J. G. O.; Pennone, J.; Anjos, F. O. M.; Souza, M. A.; Amadio, A. C.; Serrão, J. C. (International Calgary Running Symposium, August 14-17, 2014, 2014)
Evidence suggests that barefoot conditions alter the biomechanical characteristics of running 2, 3. In this study, we analyzed the influence of barefoot conditions on muscle activation intensity in 20 runners (33.2 ± 6.4 years, 72.6 ± 14.2kg, 1.72 ± 0.11m) inexperienced in barefoot locomotion. Subjects ran for 10 minutes, at 9 km/h on a treadmill, in shod and barefoot conditions. Nine data acquisitions (10 seconds each - 2600Hz) of EMGs signal were performed (EMG 100 - Lynx System) from the tibialis anterior, gastrocnemius lateralis, rectus femoris, vastus lateralis, and biceps femoris for each condition. The RMS was calculated for the stance phase. Data was normalized by the maximum voluntary isometric contraction (MVIC). A one-way ANOVA for repeated measures was performed (p <0.05). All muscles had greater EMG signals in barefoot, but only the EMG signal of the VL reached a statistically significant difference: an activation of 131% higher in barefoot (p = 0.002) than shod. Individuals who are not adapted to barefoot running, running barefoot seems to lead to a higher intensity of muscle activation compared to shod running, mainly for the VL. Considering the evidence that external forces are higher in barefoot compared to shod running for subjects not used to barefoot running1, 4, the increased muscle activation in barefoot running might be a response to an increased mechanical load, especially for the VL which is involved in impact absorption. Despite representing an intrinsic protection strategy, the greater muscle activation may influence internal load and energy expenditure in running. We conclude that barefoot running alters muscle activation intensity of the lower limbs in subjects who are not used to this condition.